Evaluation of e‐OSPE as compared to traditional OSPE: A pilot study. Issue 3 (4th March 2021) - Dutta, Atanu Kumar; Goswami, Kalyan; Murugayan, Sathish Babu; Sahoo, Sibasish; Pal, Amit; Paul, Chandramallika; Thallapaneni, Sasikala; Biswas, Soham
Abstract: Objectively Structured Clinical/Practical Examination (OSCE/OSPE) has been the backbone of the assessment system of graduate medical education for over three decades. We have developed an electronic Objectively Structured Practical Examination (e‐OSPE) in Medical Biochemistry using the freely available Google forms to mitigate the academic disruption posed by COVID‐19 pandemic in our resource‐poor setting. Ten e‐OSPE stations created, interlinked, and time‐restricted. Fifty undergraduate students appeared for the e‐OSPE examination on a prefixed date and time. Learner feedback was collected immediately after the completion of the examination. Facilitator feedback was also collected. Students' mean scores in e‐OSPE and traditional OSPE were 78.15% and 74.56%, respectively. Their difference was not statistically significant (paired t‐test two‐tailed p ‐value 0.0979). Thus, the results of e‐OSPE are reliable as compared to traditional OSPE. Bland Altman Plot revealed 92% of students had scores that were in the agreeable limit of both traditional OSPE and e‐OSPE. Both the learners and facilitators were in consensus that the online format of e‐OSPE is a good alternative for assessment (0.67 and 0.82); their experience was good (0.72 and 0.92) and conduction was well organized (0.73 and 0.86). Several suggestions were also received to make e‐OSPE even more effective. In conclusion, this pilot study showed e‐OSPE can be an effective alternative to traditional OSPE when "in‐person" evaluation is not possible such as in the current era of COVID‐19 even in resource‐limited settings.